Seven Cs of Consulting, the - Cope, Mick (Pearson Business, 2000)
The consultancy business is booming. For any consultant aiming to survive and grow in this complex world, they need to have a clear and concise change model to hand, one that can guarantee delivery of a wide range of change projects. Based around the author's 7Cs model (Client, Clarify, Create, Change, Confirm, Continue, Close), The Seven Cs of Consulting offers both budding and experienced consultants a solid and robust framework to enhance their ability to manage any consultancy assignment - from understanding the client's needs through to successful assignment completion and developing new business out of that success. With the help of the crib notes on the pull-out back pocket guide, the 7Cs model will show you how to improve your professionalism and deliver clear and demonstrable results to clients, bringing them back for more.